2019
DOI: 10.14735/amko2019201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression and Their Impact on the Quality of Life of Cancer Patients Treated with Palliative Antineoplasic Therapy – Results of the PALINT Trial

Abstract: Východiska: Úzkost, deprese a psychologický distres jsou časté syndromy u pacientů v po kročilých stadiích nádorových nemocí. V kontrastu s tím však tyto symptomy explicitně ne monitorujeme a jejich management je většinou jen na úrovni farmakoterapie. Vzhledem ke komplexitě etiologie těchto symptomů je pouze bio medicínský přístup nedostatečný a ne efektivní. Materiál a metody: Prezentujeme výsledky longitudinálního hodnocení symptomů psychického distresu, úzkosti, deprese a pocitu kvality života vzešlé ze sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Prevalence of anxiety and depression is high in advanced stages of the disease. Světláková et al found that the baseline prevalence of anxiety and depression symptomatology in 126 patients treated with palliative systemic therapy for advanced cancer was 35.9 and 56.5%, respectively [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of anxiety and depression is high in advanced stages of the disease. Světláková et al found that the baseline prevalence of anxiety and depression symptomatology in 126 patients treated with palliative systemic therapy for advanced cancer was 35.9 and 56.5%, respectively [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety occur up to 20% and 10% of patients with cancer, respectively [ 8 ], although the figures vary depending on factors such as the stage of the disease or the phase of treatment [ 8 , 9 ]. Thus, some authors estimate a higher prevalence, especially in patients with advanced cancer or palliative therapy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of anxiety and depression increases with the cancer stage. A study found that the baseline prevalence of anxiety and depression symptomatology in 126 patients treated with palliative systemic therapy for advanced cancer was 35.9 and 56.5%, respectively [6].…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of anxiety and depression symptomatology found in our study, and the strong relationship found between malnutrition and psychological distress are a robust argument for implementation of systematic screening for psychological distress, and for comprehensive psychosocial support for all patients with advanced cancer throughout the disease trajectory. The HADS questionnaire is a suitable tool for this type of screening [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation